Plasma Observations During the 7 June 2021 Ganymede Flyby From the Jovian Auroral Distributions Experiment (JADE) on Juno. Issue 23 (12th December 2022) - Allegrini, F.; Bagenal, F.; Ebert, R. W.; Louarn, P.; McComas, D. J.; Szalay, J. R.; Valek, P.; Wilson, R.; Bolton, S. J.; Connerney, J. E. P.; Clark, G.; Duling, S.; et al.
Abstract: We report on plasma observations from Juno/Jovian Auroral Distributions Experiment during the Ganymede flyby on 7 June 2021. Juno approached Ganymede from southern latitudes, passed through the wake region, then through its magnetosphere to closest approach (1, 046 km from the surface) on the night side, and then back into Jupiter's plasma disk. We describe general plasma properties in the regions explored along the trajectory. We infer that Juno traversed a region of open field lines where one end intercepts Ganymede and the other Jupiter. The observations do not support Juno crossing into the closed field line region. The ion composition near Ganymede is very different than that of the nearby plasma environment. H2 + and H3 + ions were detected near Ganymede and in the wake region. Low energy (∼0.1–1 keV) electrons are enhanced just outside the magnetopause, in the wake (inbound trajectory) and in the magnetopause boundary layer (outbound trajectory). Plain Language Summary: On 7 June 2021 the Juno mission came as close as 1, 046 km from the surface of Ganymede, the largest moon in the solar system. Similar close encounters were previously made by the Galileo mission, from which we learned much of the interaction of the moon, with its own intrinsic magnetic field, and Jupiter's magnetosphere. In this paper, we present an overview of the plasma observations, that is, ions and electrons in the lower part of the energy spectrum, made by the Jovian Auroral Distributions Experiment. We find that the ion composition near Ganymede is very different than that from Jupiter's magnetosphere. Near Ganymede, the plasma composition is dominated by molecules and ions that originate from water in the atmosphere or the surface. One surprising observation is the presence of the molecular ion H3 + inside Ganymede's magnetosphere and in a region just outside and downstream, that we call the wake. H3 + was not included in various models of Ganymede's atmosphere. Key Points: The plasma observations show that Juno crossed into the open field line region, but do not support crossing into a closed field line region The ion composition near Ganymede is very different from its local plasma environment H2 + and H3 + ions were detected inside Ganymede's magnetopause and outside in the wake region